Textual Synonymy and Copyonymy from the Perspective of Identity – Similarity – Difference - Yana A. Dudareva (СибСкрипт)
Contemporary comparative studies present synonymous relations between texts at the highest and most complex linguistic level of syntax. This approach is especially important in legal linguistics, an interdisciplinary direction that focuses on resolving real-life disputes. The practical need for new comparative and contrastive methods yields a new type of expert research, i.e., forensic examination of intellectual property. Formal and substantive similarity between texts leads to their similarity in the aspect of linguistic personality. The research featured fi e texts analyzed in line with the contemporary methods applied by linguistic experts to comparative and contrastive copyright studies. The texts had similar names but belonged to different internet bloggers. The contents demonstrated significant similarity, with almost identical formal components and minor differences. So great was the linguistic similarity that it neutralized the linguistic personality of the authors. The authors proposed copyonymy as a term for this phenomenon: texts that are so similar in form and content that the linguistic personalities of their authors disappear.